Community Organization and People's Participation: The Philippine Experience - David, Karina C. (Kasarinlan: Philippine Journal of Third World Studies; Vol 1 No 2 (1985), 2007)
This article presents concepts of community organization in today's world by restating the original assumptions behind the terms and further allowing for new concepts and methods in the effort to advance and enrich the conceptual reserve for authentic people's organizing. An analysis is given on the three types of community organizers - the apologetic, the liberal, and the liberative, explaining the unique methods of operation of each. With this explanation, the present state of communities in the Philippines is provided, along with methodological guidelines for community organizing to help with the attainment of politicalization or the recovery of the people's right to define their own reality and determine an alternative future. In order for this to occur, the importance of well-informed and systematic organizers is crucial in the process of community organization.
Keywords: Community Organization, People' s Participation, politicalization, community organizing, organizers, people' s participation, Community Development